PENDIDIKAN AGAMA ISLAM IDEAL BAGI DIFABILITAS - Mahmudin, Afif Syaiful (LP3M STAI DARUSSALAM LAMPUNG, 2017)
Education fairness being the important thing to note in this nation. The House should not be disabled again getting marginalized place. They have the same right to a decent education